Analysis of Students' Mastery of Mathematical Concepts Material for Linear Equations in Two Variables - Muthmainnah, Muthmainnah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
Mathematics learning still experiences several problems. It is still found that students have difficulty defining mathematics subject matter in their own sentences. Students also often do not know the actual applications and examples of the concepts they know. Students' ability to understand/master mathematical concepts is still low. This article aims to describe students' mastery of mathematical concepts regarding Linear Equations in Two Variables as well as efforts to improve students' mastery of mathematical concepts. This research includes qualitative research. Data collection techniques use interviews, observation, test questions, and documentation. The research results showed that students still had not mastered mathematical concepts in the material Linear Equations in Two Variables. This can be seen in students who struggle to memorize formulas and calculation processes involving large numbers. Apart from that, students do not yet understand defining concepts in writing and identify and create examples and non-examples related to the material. The efforts made to improve students' concept mastery abilities include teachers maximizing their role in the learning process and understanding various learning models that stimulate students' ability to learn with careful teaching planning by the teacher.